Is there any influence of personality disorder on the short term intensive group cognitive behavioral therapy of social phobia? - Vyskocilova, Jana; Prasko, Jan; Novak, Tomas; Pohlova, Libuse (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
BACKGROUND: The treatment of personality disorder is repeatedly reported as less successful than the treatment of patients without personality disorder. Most clinicians believe that anxiety disorder in tandem with a personality disorder often leads to longer treatment, worsens the prognosis, and thus increases treatment costs. Our study was designed to compare the short-term effectiveness of therapy in patients suffering from social phobia with and without personality disorder. METHOD: The specific aim of the study was to assess the efficacy of a 6 week therapeutic program designed for social phobia (SSRIs and CBT) in patients suffering from social phobia with comorbid personality disorder (17 patients) and social phobia without comorbid personality disorder (18 patients). The patients were regularly assessed in weeks 0, 2, 4 and 6 using the CGI (Clinical Global Improvement) for severity, LSAS (Liebowitz Social Anxiety Scale), and in self-assessments BAI (Beck Anxiety Inventory) and BDI (Beck Depression Inventory). RESULTS: Patients in both groups improved their scores in most of the assessment instruments used. A combination of CBT and pharmacotherapy proved to be the most effective treatment for patients suffering with social phobia with or without comorbid personality disorder. Treatment efficacy in patients with social phobia without personality disorder was significantly better than in the group with social phobia comorbid with personality disorder for CGI and specific inventory for social phobia - LSAS. The scores on the subjective depression inventory (BDI) also showed significantly greater decrease over the treatment in the group without personality disorder. The treatment effect between groups did not differ in subjective general anxiety scales BAI. CONCLUSION: Our study showed that patients suffering from social phobia and comorbid personality disorder showed a smaller decrease in specific social phobia symptomatology during treatment compared than patients with social phobia without personality disorders. However, a significant decrease in symptomatology occurred in personality disorder patients as well.
Keywords: poruchy osobnosti; Psychotherapy, Group; Female; Adult; dospělí; fobie; Cognitive Behavioral Therapy; Personality Disorders; kognitivně behaviorální terapie; skupinová psychoterapie; ženské pohlaví; Humans; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Phobic Disorders